Validation of Ethnochemistry-Integrated Two-Tier Items for Chemical Literacy among Pre-service Chemistry Teachers - Dyah Puspitasari Ningthias; Ermia Hidayanti; Yunita Arian Sani Anwar; Nora Listantia; Dodiy Firmansyah; Baiq Viona Olganita Sugondo (Universitas Pendidikan Mandalika, 2026)
Chemical literacy is an essential competency for preservice chemistry teachers because it supports the ability to understand chemical concepts, interpret chemical information, and apply chemistry in daily and socio-scientific contexts. However, chemical literacy assessment is often limited to conventional multiple-choice tests that do not adequately measure reasoning or contextual application. This study aimed to validate ethnochemistry-integrated two-tier multiple-choice with 10 items test for measuring chemical literacy among preservice chemistry teachers. A quantitative survey design was employed with 35 participants from a public university in West Nusa Tenggara selected through convenience sampling. This approach allowed the researchers to obtain initial empirical evidence on the psychometric quality of the ethnochemistry-integrated two-tier instrument for measuring chemical literacy among pre-service chemistry teachers. The instrument was developed by adapting chemical literacy indicators and integrating local ethnochemical contexts into two-tier items, followed by expert judgment validation. Data were collected through face-to-face, paper-based administration and analyzed using the Rasch measurement model to examine item difficulty calibration, item fit statistics, reliability, separation indices, and unidim The Wright map shows that most pre-service chemistry teachers were clustered around the mean ability range (−1 to +1 logits), indicating moderate chemical literacy, while the items were well distributed in difficulty with more challenging tasks such as Item 8 and Item 4 located at higher logits. Rasch analysis further confirmed acceptable measurement quality, with person reliability of 0.71 and Cronbach’s alpha of 0.74, item fit statistics mostly within the acceptable range (Infit MNSQ 0.78–1.43), and strong unidimensionality evidenced by 40.9% variance explained by the measures.ensionality through residual analysis. This study is novel in validating an ethnochemistry-integrated two-tier multiple-choice instrument using Rasch analysis to provide a culturally responsive and reasoning-based assessment of chemical literacy among pre-service chemistry teachers by connecting chemical concepts with local wisdom and real-life contexts.